Parenting and Military Children’s Behavior: Preliminary Findings in Military Families of New Order Era and Post-Reformation - Dindasari, Ruri; Yulianto, Bayu A. (Masyarakat: Jurnal Sosiologi, 2018)
Parenting styles within military families had implications towards their children’s behav- ior. Previous studies discussed on the parenting pattern but few has associated it with the fundamental change of Indonesian military organization post Reformation era. Therefore, this article discusses the difference of parenting pattern in the military family before and after the Reformation, and its impact towards children’s behavior. The argument is based on that change of fundamental values in the Indonesian military in New Order and post Reformation era is aligned with the changing of parenting in the military family. Those changes most likely affected the children’s behavior indirectly. In this article we use the case of parents from the military family who joined military in the New Order and post Reformation. The method used in the research for this article is qualitative method where data are gathered by conducting in-depth interviews with the respondents consist of father, mother and child from military families both from New Order era and post Reformation era who live in Depok City. This article shows that parenting style in the New Order and post Reformation military family in between democratic and authoritarian style.